Next-generation sequencing revealed recurrent ZFPM1 mutations in encapsulated papillary carcinoma of the breast - Xuguang Liu (Nature Portfolio, 2021)
Abstract Encapsulated papillary carcinoma (EPC) of the breast is a rare subtype of tumor. To date, the genetic abnormalities underlying EPC remain elusive. The purpose of this study was to gain further insight into EPC mutation profile. Forty-one EPCs diagnosed from 2015 to 2018 were included. Twenty-six EPCs were submitted to whole-exome sequencing (WES), and a 185 gene-targeted sequencing panel was designed to validate the results of the 26 EPCs that underwent WES and 15 additional cases. Recurrently mutated genes were further confirmed by Sanger sequencing. Our study revealed multiple recurrently mutated genes including PI3K-AKT-mTOR pathway genes (PIK3CA, AKT1, ULK1, MAP3K1, MAP2K4, RHOA, and PTEN) (27/41, 65.8%) and chromatin modification genes (ZFPM1, GATA3, CTCF, and KMT2C) (21/41, 51.2%) in EPC. Importantly, somatic ZFPM1 mutations existed in 9/41 (21.9%) of the EPCs. The frequency of ZFPM1 mutations in the EPCs was significantly higher than that of other tumor types. Of the nine ZFPM1 mutations, seven were frameshift mutations, and the remaining two were nonsense mutations. Moreover, a significant concurrence of ZFPM1 and PI3K-AKT-mTOR mutations were revealed in the EPCs. Of note, no TP53 mutations were detected in our EPCs, whereas it was detected in a considerable proportion of the luminal A invasive ductal carcinomas of no special type (IDC-NSTs) from TCGA. We reveal that recurrent somatic ZFPM1 mutation is characteristic of EPC and concurred with mutations in the PI3K-AKT-mTOR pathway. The distinctive genetic features of EPC might underlie its special histological structures and indolent behavior.